PRIMARY ENGLISH TEACHERS’ EFFICACY TO COPE WITH THE POOR QUALITY OF TEACHING TEXTBOOK: REFLECTIVE PRACTICE - Ratnayanti; Endah Yulia Rahayu; Nukmatus Syahria (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Reflective practices have been shown to enhance teacher self-efficacy and improve professional development. By engaging in reflective practices, teachers can identify areas where teaching resources are lacking and take action to address them, leading to improved outcomes for students. This paper examines the efficacy of reflective practices as a strategy to alleviate the poor quality of textbooks. At public primary schools, along with other unfavorable school conditions, there are shortages and low-quality textbooks and instructional resources, which reduce students' ability to learn. The shortage of teaching resources is lack of contextual and integrated to language skills. The lack of a textbook also makes it difficult for students to improve their language abilities. The textbook is ‘My Next Words’. The findings revealed that EFL teachers’ reflective practice correlates with teachers’ self-efficacy. Research has shown that reflection can augment learning by doing and increase perceived self-efficacy. The research adopts qualitative interview with experienced educators and classroom observation.